XSLT template for generating of diagram of object-oriented Petri net from the OPNML format - Petr Jedlička (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2008)
OPNML language is an open and portable format based on XML which is determined to the description of object-oriented Petri net. It is capable to express not only the structure of the analyzed system, but also its behavior and diagram. To display Petri net as a graph, there was created the template using XSLT language which defines the rules of transformation from OPNML language to SVG vector graphic format. SVG diagrams are then viewable with any web browser which supports SVG format, optionally relevant plug-in can be installed. The template also supports modular Petri nets as it is capable of creating several diagrams from one OPNML document. Individual diagrams can be interconnected via XLink links, so there is possible to move among them by mouse.